2018
DOI: 10.1007/s11682-018-9865-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of taurine neuroprotection in aged rats with traumatic brain injury

Abstract: Despite higher rates of hospitalization and mortality following traumatic brain injury (TBI) in patients over 65 years old, older patients remain underrepresented in drug development studies. Worse outcomes in older individuals compared to younger adults could be attributed to exacerbated injury mechanisms including oxidative stress, inflammation, blood-brain barrier disruption, and bioenergetic dysfunction. Accordingly, pleiotropic treatments are attractive candidates for neuroprotection. Taurine, an endogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 68 publications
(101 reference statements)
0
9
0
1
Order By: Relevance
“…Conversely, some neuroprotective strategies, such as the administration of taurine, an endogenous amino acid with antioxidant, anti-inflammatory and anti-apoptotic effects, and which is neuroprotective in adult TBI [ 221 ], is not effective following TBI in aged animals [ 219 ]. Moreover, nicotinamide, which improves functional outcome following young adult TBI [ 196 ], does not enhance functional recovery at low doses and even worsens functional deficit with higher doses [ 216 ].…”
Section: Post-traumatic Neuroinflammation and Its Consequences In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, some neuroprotective strategies, such as the administration of taurine, an endogenous amino acid with antioxidant, anti-inflammatory and anti-apoptotic effects, and which is neuroprotective in adult TBI [ 221 ], is not effective following TBI in aged animals [ 219 ]. Moreover, nicotinamide, which improves functional outcome following young adult TBI [ 196 ], does not enhance functional recovery at low doses and even worsens functional deficit with higher doses [ 216 ].…”
Section: Post-traumatic Neuroinflammation and Its Consequences In Vivomentioning
confidence: 99%
“…Administration of anti-inflammatory or neuroprotective components, like nicotinamide, taurine or epothilone, revealed no effect or even worsened tissue loss and functional deficit in aged TBI mice [ 199 , 216 , 219 ]. Altogether, these studies illustrate the complexity of age-dependent mechanism of the consequences of TBI and the necessity to consider its singularity in treatments of aged populations.…”
Section: Post-traumatic Neuroinflammation and Its Consequences In Vivomentioning
confidence: 99%
“…CCI and sham surgeries were carried out as we have previously described [26][27][28] . In brief, animals were anesthetized with isoflurane (4% induction, 2% maintenance in 2:1 Medical air:Oxygen).…”
Section: Controlled Cortical Impact (Cci) and Sham Surgeriesmentioning
confidence: 99%
“…All surgeries were carried out by a single surgeon, following methods previously reported [58][59][60] .…”
Section: Controlled Cortical Impact (Cci) and Sham Surgeriesmentioning
confidence: 99%
“…A recent study from our group showed that treatment with taurine, an anti-inflammatory, antioxidant, and anti-apoptotic therapy that had shown promise for TBI in young adult rats, did not show a similar degree of neuroprotection in elderly rats. 89 This highlights the likely influence of age on therapeutic efficacy and the critical need for inclusion of aged animal models in the drug development pipeline for TBI.…”
Section: Challenges To Modeling Tbi In Animalsmentioning
confidence: 99%